Levels of stress, depression and family functionality in hospital health personnel during the COVID-19 pandemic - Vanegas Pérez, Gabriela Marcela (2022)
Objective. To describe the levels of stress, depression and family functionality in the health team of the Central Military Hospital in Colombia and to explore possible factors associated with these conditions, in order to generate reflections on psychoeducational approaches in health personnel. Methods. Observational, analytical and cross-sectional study with a nonprobabilistic, consecutive design, in which three instruments were used: the APGAR FAMILIAR, the HADS and a questionnaire for the evaluation of stress. 229 people participated, who met the eligibility criteria. Results. The study population included a total of 229 workers, 68 % (n = 156) were women. Stress levels, according to the frequency found, were "high" and "very high" with 49.78 % (n = 114). The participants reported a normal family functionality 61.57 % (n = 141); as for the depression status, the normal level stands out 91.27 % (n = 209). Conclusions. Female personnel are identifed with higher stress indexes, resulting in a population of special attention, in addition, familyfunctionality appears as a protective factor against a potential escalation ofemotional symptoms, such as depression.